Stable centromere positioning in diverse sequence contexts of complex and satellite centromeres of maize and wild relatives - Jonathan I. Gent; Na Wang; R. Kelly Dawe (Genome Biology, 2017)
Abstract Background Paradoxically, centromeres are known both for their characteristic repeat sequences (satellite DNA) and for being epigenetically defined. Maize (Zea mays mays) is an attractive model for studying centromere positioning because many of its large (~2 Mb) centromeres are not dominated by satellite DNA. These centromeres, which we call complex centromeres, allow for both assembly into reference genomes and for mapping short reads from ChIP-seq with antibodies to centromeric histone H3 (cenH3). Results We found frequent complex centromeres in maize and its wild relatives Z. mays parviglumis, Z. mays mexicana, and particularly Z. mays huehuetenangensis. Analysis of individual plants reveals minor variation in the positions of complex centromeres among siblings. However, such positional shifts are stochastic and not heritable, consistent with prior findings that centromere positioning is stable at the population level. Centromeres are also stable in multiple F1 hybrid contexts. Analysis of repeats in Z. mays and other species (Zea diploperennis, Zea luxurians, and Tripsacum dactyloides) reveals tenfold differences in abundance of the major satellite CentC, but similar high levels of sequence polymorphism in individual CentC copies. Deviation from the CentC consensus has little or no effect on binding of cenH3. Conclusions These data indicate that complex centromeres are neither a peculiarity of cultivation nor inbreeding in Z. mays. While extensive arrays of CentC may be the norm for other Zea and Tripsacum species, these data also reveal that a wide diversity of DNA sequences and multiple types of genetic elements in and near centromeres support centromere function and constrain centromere positions.